Sacrificial Anode Cathodic Protection Remote Monitoring And Control Using Labview And Micaz Motes - Zeki Al−faiz, Mohammed; Saadi Mezher, Liqaa (Journal of Engineering and Sustainable Development, 2014)
The Cathodic Protection system (CP) is used for the monitoring system of oil pipeline via Wireless Sensor devices to prevent corrosion. In this paper the use of Sacrificial Anode Cathodic Protection (SACP) system was presented and how they can be developed to prevent the corrosion. The aim of developing a CP system is to provide control over oil pipelines and to reduce the incidence of corrosion. The proposed system integrates the technology of Wireless Sensor Network (WSN) in order to collect potential data and to realize remote data transmission. Three cases had been studied, the first case is a normal situation when there is not find any problem in oil pipeline, the second case is in the event of a malfunction in the values of voltage by a simple increase or decrease in this case possible controller by the observer in the remote control room. The third case is in the event of a serious defect in the pipe and be output either smuggling operation or malfunction in the anode. Each one of the three studies cases use nine Wireless Sensors (WS’s), three Remot Terminal Units (RTU’s) and one Base Station (BS). LabVIEW 2010 program was used as the tool to build the simulation.....